Placental plastics in young women from general population correlate with reduced foetal growth in IUGR pregnancies - Amereh, Fatemeh; Amjadi, Nooshin; Mohseni-Bandpei, Anoushiravan; Isazadeh, Siavash; Mehrabi, Yadollah; Eslami, Akbar; Naeiji, Zahra; Rafiee, Mohammad (Environmental pollution (1987), 2022)
Constant exposure to plastics particulates has raised concerns against human health, particularly when it comes to birth outcomes. The present study explores the first appraisal of plastic particles in fresh human placenta and its association with foetal growth in neonates. Specifically, 43 pregnant women from general population were selected and their placentas were analyzed by digital microscopy and Raman microspectroscopy for microplastics (MPs <5 mm). We used regression analysis to estimate associations between MPs count in placenta and neonatal anthropometric measurements. MPs were found in all (13 out of 13) intrauterine growth restriction (IUGR) pregnancies and their average abundance ranged from 2 to 38 particles per placenta, but were less than limit of detection (LOD) in normal pregnancies except three out of 30 subjects. This study is one of very few that detected MPs in human placenta in which particles <10 μm were the most abundant in both IUGR and normal pregnancies, accounting for up to 64%. Fragments clearly prevailed at normal pregnancies and fragments together with fibers predominated at IUGR placentas. Despite four different polymers forming the MPs being identified, the majority of MPs comprised of PE (polyethylene) and PS (polystyrene). Inverse associations between MPs exposure and birth outcomes were observed in terms of birth weight (r = - 0.82, p < 0.001), length (r = - 0.56, p < 0.001), head circumference (r = - 0.50, p = 0.001), and 1-min Apgar score (r = - 0.75, p < 0.001) among those with IUGR, compared to those that were nominated as normal pregnancies. While it seems plastic particles may affect placental-foetal interrelationship, the pattern of associations between their content in placenta and birth outcomes, however, shows evidence of a nonlinear or nonmonotonic dose response possibly through perturbation of gas and nutrients exchange which is worth future investigation. [Display omitted] •The presence and quantity of plastic particles in fresh human placentas was demonstrated.•Size, shape and elemental composition of these exogenous particles were identified.•Inverse associations were found between MPs and neonatal anthropometric measurements.•Plastic particles may affect placental-fetal interrelationship in IUGR fetuses.